Adverse event reports of seizure for insomnia medication from 1967 to 2023 - Tae Hyeon Kim; Kyeongmin Lee; Jiyoung Hwang; Suhyun Lee; Hyesu Jo; Hanseul Cho; Hayeon Lee; Hye Jeong Baek; Jiseung Kang; Christa J. Nehs; Guillaume Fond; Laurent Boyer; et al. (Scientific Reports)
Abstract Insomnia may negatively impact seizure control; however, the corresponding evidence remains limited. This study analyzed the seizure risk associated with various insomnia medications using a comprehensive pharmacovigilance database and identified safe options for patients at high risk of seizures. VigiBase, a database of adverse drug reaction reports from over 140 countries, comprises 35 million reports published from 1967 to 2023. Medications for insomnia include benzodiazepines, Z-drugs, antidepressants, atypical antipsychotics, first-generation H1 antagonists, orexin receptor agonists, melatonin, and melatonin receptor agonists. We assessed the association between insomnia medications and seizure risk by analyzing the reported odds ratio (ROR) with 95% confidence intervals (CI) and the information component (IC) with IC025. In total, 17,967 cases of seizures associated with insomnia medications were reported, revealing a significant association (ROR, 2.12 [95% CI, 2.09 to 2.15]; IC, 1.05 [IC025, 1.03]). Based on the mechanism of action, seizures were significantly associated with benzodiazepines (ROR, 2.56 [95% CI, 2.49 to 2.64]; IC, 1.34 [IC025, 1.29]), Z-drugs (ROR, 1.58 [1.49 to 1.69]; IC, 0.66 [0.56]), antidepressants (ROR, 2.52 [2.43 to 2.61]; IC, 1.32 [1.26]), atypical antipsychotics (ROR, 1.92 [1.88 to 1.97]; IC, 0.93 [0.89]), first-generation H1 antagonists (ROR, 2.08 [1.98 to 2.19]; IC, 1.05 [0.96]), and melatonin (ROR, 1.81 [1.49 to 2.20]; IC, 0.84 [0.51]). In contrast, orexin receptor antagonists (ROR, 0.81 [95% CI, 0.61 to 1.07]; IC, − 0.30 [IC025, − 0.77]) and melatonin receptor agonists (ROR, 1.20 [0.80 to 1.81]; IC, 0.26 [− 0.44]) showed no significant association with seizures. Although the disproportionality analysis did not allow causal interpretation, our study highlights significant variations in seizure signal among insomnia medications.